2014
DOI: 10.1007/s12263-014-0447-x
|View full text |Cite
|
Sign up to set email alerts
|

Dietary inflammatory index and inflammatory gene interactions in relation to colorectal cancer risk in the Bellvitge colorectal cancer case–control study

Abstract: Chronic inflammation is an important factor in colorectal carcinogenesis. However, evidence on the effect of pro-inflammatory and anti-inflammatory foods and nutrients is scarce. Moreover, there are few studies focusing on diet-gene interactions on inflammation and colorectal cancer (CRC). This study was designed to investigate the association between the novel dietary inflammatory index (DII) and CRC and its potential interaction with polymorphisms in inflammatory genes. Data from the Bellvitge Colorectal Can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
80
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
9

Relationship

7
2

Authors

Journals

citations
Cited by 93 publications
(91 citation statements)
references
References 31 publications
11
80
0
Order By: Relevance
“…Of these, one showed positive associations with lung cancer risk (17), 3 with colorectal cancer risk (19,23,25), and another with CVD risk (14). In addition, nonprospective case-control investigations found positive associations with colorectal (22,27), prostate (20,28), esophageal (13,29), and pancreatic (21) cancers and asthma (26). However, no relation has been observed between the DII and breast cancer (16).…”
Section: Discussionmentioning
confidence: 99%
“…Of these, one showed positive associations with lung cancer risk (17), 3 with colorectal cancer risk (19,23,25), and another with CVD risk (14). In addition, nonprospective case-control investigations found positive associations with colorectal (22,27), prostate (20,28), esophageal (13,29), and pancreatic (21) cancers and asthma (26). However, no relation has been observed between the DII and breast cancer (16).…”
Section: Discussionmentioning
confidence: 99%
“…However, our previous experience with using the DII indicates that those conditions that we know from other lines of research (e.g., laboratory animal experiments) to be most strongly related to inflammation tend to produce the most strongly positive results. Most notably, this includes colorectal cancer (which, because of its relatively high incidence, drives digestive-tract cancer rates) [32,[34][35][36], pancreatic cancer [37], and asthma, lung and other respiratory conditions [28,31]. In contrast, results have been equivocal for factors related to metabolic syndrome and thereby for cardiovascular outcomes as well [25,26,29].…”
Section: Discussionmentioning
confidence: 99%
“…Thus far, the DII has been found to be associated with C-reactive protein [24,25], interleukin-6 [26][27][28], and homocysteine [26]. Additionally, DII has been shown to be associated with glucose intolerance and dyslipidemia components of the metabolic syndrome [25,29], anthropometric measurements in Spain [30], asthma in Australia [28], respiratory conditions in Italy [31], bone mineral density among postmenopausal women in Iran [28], colorectal cancer in two case-control studies in Spain and Italy [32,33], and three cohort studies in the USA [34][35][36], pancreatic [37], prostate [38,39] and esophageal cancers [40,41] and mortality in a cohort among US women [42].…”
Section: Introductionmentioning
confidence: 99%
“…We previously found that food frequency questionnaire (FFQ)-derived DII scores were significantly associated with inflammatory biomarkers, where higher DII scores (representing more pro-inflammatory diets) were positively associated with interleukin-6 (IL-6), tumor necrosis factor alpha receptor 2 (TNFα-R2) and high sensitivity C-reactive protein (hs-CRP) in a subset of women in the Women’s Health Initiative (WHI) (unpublished results: Tabung, Steck, Zhang, Ma, Liese, Agalliu, et al, 2014). In addition, we observed that a higher DII score was associated with increased risk of colorectal cancer in the Iowa Women’s Health Study, with a hazard ratio (HR) of 1.20 [95% confidence interval (CI), 1.01–1.43] comparing the highest with the lowest DII quintile (22) as well as in the Bellvitge Colorectal Cancer Case-control Study where the odds ratio for the fourth quartile compared to the first was 1.65 (95%CI, 1.05–2.60) (23). Our objective in the current study was to examine whether pro-inflammatory diets, as measured by the DII, are associated with increased risk of colorectal cancer in the WHI, a larger, more racially and geographically diverse population of postmenopausal women in the United States.…”
Section: Introductionmentioning
confidence: 99%